Protocadherin B9 promotes resistance to bicalutamide and is associated with the survival of prostate cancer patients. Issue 2 (16th October 2018) - Sekino, Yohei; Oue, Naohide; Mukai, Shoichiro; Shigematsu, Yoshinori; Goto, Keisuke; Sakamoto, Naoya; Sentani, Kazuhiro; Hayashi, Tetsutaro; Teishima, Jun; Matsubara, Akio; Yasui, Wataru
Abstract : Background Prostate cancer (PCa) is a common malignancy worldwide and is the second leading cause of cancer death in men. The standard therapy for advanced PCa is androgen deprivation therapy (ADT). Although ADT, including bicalutamide treatment, is initially effective, resistance to bicalutamide frequently occurs and leads to the development of castration‐resistant PCa. Thus, clarifying the mechanisms of bicalutamide resistance is urgently needed. We designed this study to assess the expression and function of PCDHB9, which encodes the protocadherin B9 protein. Methods The expression of PCDHB9 was determined using immunohistochemistry and a qRT‐PCR. The effects of the overexpression or knockdown of PCDHB9 on cell growth, migration, adhesion were evaluated. To evaluate the PCDHB9‐mediated effects in PCa, we performed a gene expression analysis using DU145 transfected with PCDHB9. We examined the effects of PCDHB9 inhibition on bicalutamide resistance. Results The qRT‐PCR revealed that the expression of PCDHB9 was much higher in PCa than that in non‐neoplastic prostate tissues. In 152 clinically localized PCa cases immunohistochemistry showed that 59% of PCa cases were positive for protocadherin B9. A Kaplan‐Meier analysis showed that the high expression of protocadherin B9 was associated with PSA recurrence after radical prostatectomy. A functional analysis showed that PCDHB9 modulated cell migration and adhesion. We also found that PCDHB9 induced the expression of ITGB6 based on a gene expression analysis. The effect of PCDHB9 inhibition on bicalutamide sensitivity was examined using MTT assays. The IC50 value of PCDHB9 siRNA‐transfected PCa cells was significantly lower than that of negative control siRNA‐transfected cells. Furthermore, immunohistochemical staining of protocadherin B9 in 74 PCa patients who were treated with androgen depletion therapy, including bicalutamide treatment, demonstrated that the high expression of protocadherin B9 was significantly associated with poor overall survival. Conclusions PCDHB9 plays an important role in the progression of PCa and bicalutamide resistance. Collectively, our results suggest that PCDHB9 targeted therapy may be more effective than bicalutamide alone.